2016
DOI: 10.3389/fncom.2016.00080
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tempo and Rhythmic Unit in Musical Emotion Regulation

Abstract: This article is based on the assumption of musical power to change the listener's mood. The paper studies the outcome of two experiments on the regulation of emotional states in a series of participants who listen to different auditions. The present research focuses on note value, an important musical cue related to rhythm. The influence of two concepts linked to note value is analyzed separately and discussed together. The two musical cues under investigation are tempo and rhythmic unit. The participants are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 40 publications
(45 reference statements)
3
40
0
Order By: Relevance
“…The role of specific musical structures (rhythm and pitch) in K.448 was studied in rodents and humans (85), whereas high periodicity was proposed to account for the antiseizure effects (73). Musical tempo modulate emotions (113) which can in turn affect pain processing (114,115). Exposure to K.448 was shown to activate the parasympathetic nervous system (33).…”
Section: Translational Implications Of Studying Enriched Environmentmentioning
confidence: 99%
“…The role of specific musical structures (rhythm and pitch) in K.448 was studied in rodents and humans (85), whereas high periodicity was proposed to account for the antiseizure effects (73). Musical tempo modulate emotions (113) which can in turn affect pain processing (114,115). Exposure to K.448 was shown to activate the parasympathetic nervous system (33).…”
Section: Translational Implications Of Studying Enriched Environmentmentioning
confidence: 99%
“…Information that identifies a user' affective states is used to adapt the behavior of an application to keep the user satisfied or engaged. For example, some studies found neurophysiological responses in theta and alpha frequency bands to differentiate between episodes of frustrating and normal game play (Shergill et al, 2013 ) or even musical emotion regulation (Fernández-Sotos et al, 2016 ; Martínez-Rodrigo et al, 2017 ).…”
Section: Most Important Challenges In Human-avatar Symbiosis For Amentioning
confidence: 99%
“…Another limitation was that in this study the use of music was limited only as a structural resource in the physical activity session and as an accompaniment during the development of the exercises, so the effect on the study variables was not measured. However, research in neuropsychology has used music for other purposes such as controlling emotions, improving quality of life, self-care, and behavior, through the reactions to specific musical signals such as melody, harmony, tempo, doorbell music, among others (Costa et al, 2012;Castillo et al, 2014;Fernández-Sotos et al, 2016). Therefore, it is recommended for future research to consider determining the influence of music on physical and psychological variables.…”
Section: Discussionmentioning
confidence: 99%